Rad6–Bre1-mediated H2B ubiquitination regulates telomere replication by promoting telomere-end resection. Issue 6 (9th February 2017) - Wu, Zhenfang; Liu, Jun; Zhang, Qiong-Di; Lv, De-Kang; Wu, Nian-Feng; Zhou, Jin-Qiu
Abstract: Rad6 and Bre1, ubiquitin-conjugating E2 and E3 enzymes respectively, are responsible for histone H2B lysine 123 mono-ubiquitination (H2Bub1) in Saccharomyces cerevisiae . Previous studies have shown that Rad6 and Bre1 regulate telomere length and recombination. However, the underlying molecular mechanism remains largely unknown. Here we report that H2BK123 mutation results in telomere shortening, while inactivation of Ubp8 and/or Ubp10, deubiquitinases of H2Bub1, leads to telomere lengthening in Rad6–Bre1-dependent manner. In telomerase-deficient cells, inactivation of Rad6–Bre1 pathway retards telomere shortening rate and the onset of senescence, while deletion of UBP8 and/or UBP10 accelerates senescence. Thus, Rad6–Bre1 pathway regulates both telomere length and recombination through its role in H2Bub1. Additionally, inactivation of both Rad6–Bre1–H2Bub1 and Mre11–Rad50–Xrs2 (MRX) pathways causes synthetic growth defects and telomere shortening in telomerase-proficient cells, and significantly accelerates senescence and eliminates type II telomere recombination in telomerase-deficient cells. Furthermore, RAD6 or BRE1 deletion, or H2BK123R mutation decreases the accumulation of ssDNA at telomere ends. These results support the model that Rad6–Bre1–H2Bub1 cooperates with MRX to promote telomere-end resection and thus positively regulates both telomerase- and recombination-dependent telomere replication. This study provides a mechanistic link between histone H2B ubiquitination and telomere replication.